Analysis of pacing strategy selection in elite 400-m freestyle swimming - Mauger, A. R.; Neuloh, J.; Castle, P. C. (Medicine & Science in Sports & Exercise, 2012)
Introduction: Pacing strategy selection can exert a significant influence on performance in events where time to completion is the measure of success. However, few studies exist examining pacing in elite sport, with even less examining pacing in swimming.